2(x+2)=-2(3x-1)

Simple and best practice solution for 2(x+2)=-2(3x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x+2)=-2(3x-1) equation:


Simplifying
2(x + 2) = -2(3x + -1)

Reorder the terms:
2(2 + x) = -2(3x + -1)
(2 * 2 + x * 2) = -2(3x + -1)
(4 + 2x) = -2(3x + -1)

Reorder the terms:
4 + 2x = -2(-1 + 3x)
4 + 2x = (-1 * -2 + 3x * -2)
4 + 2x = (2 + -6x)

Solving
4 + 2x = 2 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
4 + 2x + 6x = 2 + -6x + 6x

Combine like terms: 2x + 6x = 8x
4 + 8x = 2 + -6x + 6x

Combine like terms: -6x + 6x = 0
4 + 8x = 2 + 0
4 + 8x = 2

Add '-4' to each side of the equation.
4 + -4 + 8x = 2 + -4

Combine like terms: 4 + -4 = 0
0 + 8x = 2 + -4
8x = 2 + -4

Combine like terms: 2 + -4 = -2
8x = -2

Divide each side by '8'.
x = -0.25

Simplifying
x = -0.25

See similar equations:

| 130=5(15+x) | | 1.30*40=x | | y=[x-(1+2i)][x-(1-2i)] | | 3.5x=x+5 | | (x-17)/(x-20)3 | | (2X-12)(x+5)=0 | | 10=x-4x+2 | | N=31+14 | | 10+6x=x-30 | | 3d-4=6d-11 | | x*x×x/2 | | -3n+3=27 | | n-(-130)=-2 | | 6(7-1)+8=32 | | -3x+5-7x=2-4x+3 | | Log(y)=2.5 | | =6a^3+10a^2-24a | | 2p-2/p×5p^2/7p-7 | | 4(9+5x)=36 | | 7-4x=28 | | 15-12*3= | | -3x+5-7x=2-4+3 | | k/5-4=-2 | | Y-3=1+3 | | 3(x-6)=-x+2(x-6) | | (x^2-1)(x^2+8x+12)=0 | | 49x4/7 | | (X-1)(x+14)=0 | | 5/2/7 | | p/3+5=7 | | 3x+(-7x-3)=-153 | | 8-2-Y=6-4 |

Equations solver categories